THE INFLUENCE OF TAX SYSTEM AND TAX FAIRNESS ON TAX EVASION - Widya Indah Nurmalasari (Media Bina Ilmiah, 2025)
Tax evasion is an illegal act carried out by taxpayers to avoid the obligation to pay taxes in full or at all, by hiding income, manipulating financial reports, or avoiding tax obligations through fraudulent means. This study aims to analyze the influence of the tax system and tax fairness on tax evasion. This study uses a quantitative approach with a causality research type. The population and sample in this study were 70 Taxpayers in the City of Surabaya. The analysis in this study uses Partial Least Square (PLS) analysis. The results of this study show that: (1) The Taxation System has a significant negative effect on Tax Evasion, and (2) Tax Justice has a significant negative effect on Tax Evasion